Improving the identification of genitourinary syndrome of menopause through the utilization of the Day-to-Day Impact of Vaginal Aging questionnaire. Issue 11 (November 2020) - Mastroianni, Jennie; Thompson, Julie A.; Shifren, Jan L.; Zuckerman, Andrea L.; Pereira, Katherine
Abstract: Objective: Genitourinary syndrome of menopause (GSM) affects nearly 50% of postmenopausal women. Yet women fail to recognize GSM as a chronic condition and are reluctant to discuss their vaginal or sexual complaints with a health care provider. This quality improvement project implemented the Day-to-Day Impact of Vaginal Aging (DIVA) questionnaire to improve the identification and diagnosis of GSM in women ≥ 45 years of age presenting for an annual wellness examination or a vulvovaginal/genitourinary complaint. Methods: From October 2019 to February 2020, the DIVA questionnaire was distributed in a large women's health practice setting to women ≥ 45 years of age, for completion before their annual wellness visit or for evaluation of a GSM-related complaint. GSM diagnosis rates during the implementation period were compared with diagnosis rates during a 4-month period immediately preceding the implementation. Data collected during the implementation period were examined to evaluate if GSM diagnosis was more likely in patients who completed the DIVA questionnaire when compared to those women who did not complete the questionnaire. Results: Of the 175 women who met the inclusion criteria, 113 completed the DIVA questionnaire. Completion of the DIVA questionnaire demonstrated a relative percentage increase in GSM diagnosis by 30.7% when compared to the 4-month preimplementation period (10.1% to 13.2%, P = 0.231). This change was not statistically significant. During the implementation period, a statistically significant difference in GSM diagnosis was observed for patients who completed the DIVA questionnaire when compared to those patients who did not complete the questionnaire (37.2% vs 9.7%, P < 0.001). When results were stratified by visit type, women presenting for an annual wellness visit who completed the DIVA questionnaire had a higher GSM diagnosis rate than those who did not complete the questionnaire (37.2% vs 10%, P < 0.001). When results were stratified by menopausal status, GSM diagnosis rates were also more likely for postmenopausal women who completed the DIVA questionnaire when compared to those who did not complete the questionnaire (44.2% vs 8.5%, P < 0.001). Conclusions: The DIVA questionnaire is a brief, but comprehensive screening tool that can increase GSM identification and treatment, particularly for postmenopausal, and midlife women presenting for an annual wellness visit in a busy women's health practice setting. N/A: Video Summary: http://links.lww.com/MENO/A655 . Abstract : Supplemental Digital Content is available in the text